Precise Online Electrochemical Impedance Spectroscopy Strategies for Li-Ion Batteries - Islam, S. M. Rakiul; Park, Sung-Yeul (IEEE transactions on industry applications, 2020)
This article presents an online electrochemical impe-dance spectroscopy (EIS) technique for a Li-Ion battery. A frequency sweeping method and a precise impedance measurement algorithm are used for the proposed online EIS technique. The proposed algorithm consists of fast Fourier transformations, peak amplitudes, and phase difference estimations. Additional instrumentation with offset clipping and amplifying circuits expand the accuracy of the signal measurement. The offset clipping circuit increases the ripple to measurement voltage ratio without phase delay. The amplifying circuit gives more resolution for the ripple voltage. The proposed instrumentation ensures the precise measurement of ripple voltage and current. The proposed impedance measurement algorithm fulfills the precision level required for industrial Li-Ion battery. To validate the proposed approach, a 40-Ah 13.6 V Li-Ion battery charger was built using a synchronous buck converter and an Opal-RT based controller. The proposed spectroscopy technique will be useful to track and estimate internal electrochemical conditions of a battery.